Plant response to sunflower seeds to osmotic conditioning - Camila Santos Barros de Morais (Semina: Ciências Agrárias, 2014)
The aim of this study was to evaluate the effect of seeds osmotic conditioning in seedlings emergence and plants performance of sunflower. Three lots of seeds sunflower (Catissol), was submited to osmotic conditioning with polyethylene glycol solution, –2,0 MPa in aerated system, under 15 ºC for 8 hour and then was evaluated for germination tests and vigour. Under filed conditions was conducted emergency evaluations of seedling, plants development as well as the productivity and seeds quality, and the accumulation of nutrients in the seeds. The osmotic conditioning improve the survival of seedling, the dry matter mass to aerial part of plants from 60 days after sowing and oil content, in lots with low seeds physiological quality. The osmotic conditioning not increase the seeds yield but promotes the vigour of seeds produced, regardless of the lot used for sowing seeds.